Economics of Potato Seed Production– an Analytical Study from Terai Zone of West Bengal - Layek, Nityananda; Mula, Gobinda (International Journal of Economic Plants, 2021)
The study was conducted to analyze the economics of cultivation of potato seed in respect of technical efficiency and allocative efficiency in Terai zone of West Bengal, India based on primary data collected during September 2018 to March, 2019. The multistage sampling technique was used to select 80 potato seed grower as respondent. Total variable cost of cultivation (Rs. acre-1) was 47662.70 and 46098.94, respectively for seed and conventional production. Net return (GI-Cost C3) in seed production revealed ` 29931.67 acre-1 which was 53.13% higher than conventional potato production. The input-output ratio (based on Cost C3) for seed production was examined as 1:1.51. The contribution of different used resources to the variation of income (yield) was found 90% (R2=0.900). The factors viz., seed and organic fertilizers found significant at 5% and human labour at 1% level. Low price of output, diseases and pest attack, high price of inputs, shortage of labour and irrigation were major problems in potato seed production. Hence, to increase production potential of potato seed at the farmers level, the availability of quality seed is to be ensured along with proper infrastructure, guidance and training facilities.